Changed reactivity of secondary hydroxy groups in C8-modified adenosine – lessons learned from silylation - Frommer, Jennifer; Müller, Sabine (Beilstein Journal of Organic Chemistry, 2020)
Synthesis of site-specifically modified oligonucleotides has become a major tool for RNA structure and function studies. Reporter groups or specific functional entities are required to be attached at a pre-defined site of the oligomer. An attractive strategy is the incorporation of suitably functionalized building blocks that allow post-synthetic conjugation of the desired moiety. A C8-alkynyl-modified adenosine derivative was synthesized, reviving an old synthetic pathway for iodination of purine nucleobases. Silylation of the C8-alkynyl-modified adenosine revealed unexpected selectivity of the two secondary sugar hydroxy groups, with the 3'-O-isomer being preferentially formed. Optimization of the protection scheme lead to a new and economic route to the desired C8-alkynylated building block and its incorporation in RNA.
Keywords: nucleoside chemistry; protecting groups; RNA synthesis; Sonogashira reaction

(untitled) - Teplova, M.; Falschlunger, C.; Krasheninina, O.; Egger, M.; Ren, A.; Patel, D. J.; Micura, R. (Angew. Chem., Int. Ed., 2020)

(untitled) - Steinmetzger, C.; Bäuerlein, C.; Höbartner, C. (Angew. Chem., Int. Ed., 2020)

(untitled) - Fuchs, E.; Falschlunger, C.; Micura, R.; Breuker, K. (Nucleic Acids Res., 2019)

(untitled) - Vušurović, N.; Altman, R. B.; Terry, D. S.; Micura, R.; Blanchard, S. C. (J. Am. Chem. Soc., 2017)

(untitled) - Neuner, E.; Frener, M.; Lusser, A.; Micura, R. (RNA Biol., 2018)

(untitled) - Frommer, J.; Appel, B.; Müller, S. (Curr. Opin. Biotechnol., 2015)

(untitled) - Chen, B.; Longhini, A. P.; Nußbaumer, F.; Kreutz, C.; Dinman, J. D.; Dayie, T. K. (Chem. – Eur. J., 2018)

(untitled) - Graber, D.; Moroder, H.; Micura, R. (J. Am. Chem. Soc., 2008)

(untitled) - Juliusson, H. Y.; Segler, A.-L. J.; Sigurdsson, S. T. (Eur. J. Org. Chem., 2019)

(untitled) - Cetiner, E. C.; Jonker, H. R. A.; Helmling, C.; Gophane, D. B.; Grünewald, C.; Sigurdsson, S. T.; Schwalbe, H. (J. Biomol. NMR, 2019)

(untitled) - Tong, A. K.; Ju, J. (Nucleic Acids Res., 2002)

(untitled) - Clark, K. D.; Zhu, C.; Anderson, J. L. (Anal. Chem. (Washington, DC, U. S.), 2019)

(untitled) - Rublack, N.; Nguyen, H.; Appel, B.; Springstubbe, D.; Strohbach, D.; Müller, S. (J. Nucleic Acids, 2011)

(untitled) - Proudnikov, D.; Mirzabekov, A. (Nucleic Acids Res., 1996)

(untitled) - Ghosh, S. S.; Kao, P. M.; McCue, A. W.; Chappelle, H. L. (Bioconjugate Chem., 1990)

(untitled) - El-Sagheer, A. H.; Brown, T. (Chem. Soc. Rev., 2010)

(untitled) - Kim, E.; Koo, H. (Chem. Sci., 2019)

(untitled) - Kath-Schorr, S. (Top. Curr. Chem., 2016)

(untitled) - Gao, M.; Gnutt, D.; Orban, A.; Appel, B.; Righetti, F.; Winter, R.; Narberhaus, F.; Müller, S.; Ebbinghaus, S. (Angew. Chem., Int. Ed., 2016)

(untitled) - Sindbert, S.; Kalinin, S.; Nguyen, H.; Kienzler, A.; Clima, L.; Bannwarth, W.; Appel, B.; Müller, S.; Seidel, C. A. M. (J. Am. Chem. Soc., 2011)

(untitled) - Müller, S. (Ann. N. Y. Acad. Sci., 2015)

(untitled) - Hieronymus, R.; Müller, S. (Ann. N. Y. Acad. Sci., 2019)

(untitled) - Frommer, J.; Müller, S. (Angew. Chem., Int. Ed., 2020)

(untitled) - Strohbach, D.; Novak, N.; Müller, S. (Angew. Chem., Int. Ed., 2006)

(untitled) - Tierney, M. T.; Grinstaff, M. W. (Org. Lett., 2000)

(untitled) - Nandi, B.; Pattanayak, S.; Paul, S.; Sinha, S. (Eur. J. Org. Chem., 2013)

(untitled) - Moriarty, R. M.; Epa, W. R.; Awasthi, A. K. (Tetrahedron Lett., 1990)

(untitled) - Hayakawa, H.; Haraguchi, K.; Tanaka, H.; Miyasaka, T. (Chem. Pharm. Bull., 1987)

(untitled) - Somoza, Á. (Chem. Soc. Rev., 2008)

(untitled) - Neuner, S.; Santner, T.; Kreutz, C.; Micura, R. (Chem. – Eur. J., 2015)

(untitled) - Hakimelahi, G. H.; Proba, Z. A.; Ogilvie, K. K. (Can. J. Chem., 1982)

(untitled) - Altona, C.; Sundaralingam, M. (J. Am. Chem. Soc., 1973)

(untitled) - Serebryany, V.; Beigelman, L. (Tetrahedron Lett., 2002)

(untitled) - Shishodia, S.; Zhang, D.; El-Sagheer, A. H.; Brown, T.; Claridge, T. D. W.; Schofield, C. J.; Hopkinson, R. J. (Org. Biomol. Chem., 2018)

(untitled) - Furusawa, K.; Ueno, K.; Katsura, T. (Chem. Lett., 1990)

(untitled) - Flamme, M.; McKenzie, L. K.; Sarac, I.; Hollenstein, M. (Methods, 2019)

(untitled) - Riml, C.; Lusser, A.; Ennifar, E.; Micura, R. (J. Org. Chem., 2017)

(untitled) - Gundlach, C. W., IV; Ryder, T. R.; Glick, G. D. (Tetrahedron Lett., 1997)

(untitled) - Ching, S. M.; Tan, W. J.; Chua, K. L.; Lam, Y. (Bioorg. Med. Chem., 2010)

(untitled) - Frommer, J.; Karg, B.; Weisz, K.; Müller, S. (Org. Biomol. Chem., 2018)